2015
DOI: 10.15226/2374-6874/5/1/00144
|View full text |Cite
|
Sign up to set email alerts
|

Relations between the Experience of the Yips and Athletes’ Psychological Growth

Abstract: Traditionally, the 'yips' has been known as a movement disorder observed when a golfer is putting (e.g., [1]) and according to a survey that McDaniel, et al. [1] conducted on 1050 golfers, there was a 42% response rate and 28% reported that they had experienced the yips. Furthermore, according to a survey that Smith, et al. [2] conducted on 1031 golfers, 541 (52%) responded that they had experienced the yips in the past. On the other hand, baseball players also suffer from the yips in the same way[3, 4]. Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…On the other hand, scores were not significantly higher for the yips group on any subscale compared to those for the other groups. Matsuda et al (2018) correlated these findings with the findings of a previous study and pointed out that the psychological growth observed in people who have experienced the yips is not merely because of the experience of the yips, as overcoming the yips also plays an important role in growth.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, scores were not significantly higher for the yips group on any subscale compared to those for the other groups. Matsuda et al (2018) correlated these findings with the findings of a previous study and pointed out that the psychological growth observed in people who have experienced the yips is not merely because of the experience of the yips, as overcoming the yips also plays an important role in growth.…”
Section: Introductionsupporting
confidence: 82%
“…However, in the study by Matsuda et al (2018), only the relevance between the experience of the yips, overcoming the affliction, and psychological growth as an athlete is demonstrated; the kind of pathway that brings about these associations (e.g., the process by which an athlete experiences the yips and overcomes the affliction, then demonstrates psychological growth) has not been verified. By clarifying the process just described, this study can help athletes who have experienced the yips or an athlete's coach to reconsider how they recognize and cope with the yips.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation